Purinergic signalling displays a pro-inflammatory profile in spleen and splenic lymphocytes of Rhamdia quelen fed with a diet contaminated by fungal mycotoxin: Involvement on disease pathogenesis - Baldissera M.D. (2018)
© 2018 Elsevier LtdThe spleen is an important secondary lymphatic organ that plays a key role in the immune and inflammatory responses of teleost fish. The purinergic signalling has been associated to these types of responses under pathological conditions by the regulation of extracellular adenosine triphosphate (ATP) and its metabolite adenosine (Ado), where both exert potent pro-inflammatory and anti-inflammatory profiles, respectively. The exact pathway involved on the immunotoxic effects of aflatoxin B1 (AFB1) in fish fed with diets containing this mycotoxin remains poorly understood. Thus, the aim of this study was to evaluate whether purinergic signalling exerts anti or pro-inflammatory effects in spleen and splenic lymphocytes of Rhamdia quelen fed with a diet contaminated by AFB1. Ectonucleoside triphosphate diphosphohydrolase (NTPDase) activity (ATP as substrate) decreased in spleen and splenic lymphocytes of fish fed with an AFB1-contaminated diet on day 21 post-feeding compared to fish fed with a basal diet; while adenosine deaminase (ADA) activity increased. No differences were observed between groups or over time regarding NTPDase (adenosine diphosphate as substrate) and 5′-nucleotidase activities. In summary, the purinergic signalling can be a pathway involved in the impairment of the immune and inflammatory responses in fish fed with an AFB1-contaminated diet, contributing to the immunotoxic effects of AFB1 in spleens of fish.